2022
DOI: 10.1186/s12906-022-03578-1
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin identified from Citrus extracts potently inhibits HCV genotype 3a NS3 protease

Abstract: Background Hepatitis C virus infection is the main cause of liver ailments across the globe. Several HCV genotypes have been identified in different parts of the world. Effective drugs for combating HCV infections are available but not affordable, particularly to infected individuals from resource-limited countries. Hence, cost-effective drugs need to be developed against important HCV drug targets. As Citrus fruits naturally contain bioactive compounds with antiviral activities, the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 85 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Molecular docking study found, it inhibit NS3 protease by establishing hydrogen bonds with active site residues (His57, Asp81 and Ser139). 35 Isolation from Taxillus sutchuenensis herba identified isosakuranetin (23), homoeriodictyol-7-O-β-D-glucopyranoside (24) and viscumneoside I (25). These compounds inhibit NS3 protease with IC50 values of 234.4±2.2 mM, 68.9±0.4 mM and 62.3±2.0 mM, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking study found, it inhibit NS3 protease by establishing hydrogen bonds with active site residues (His57, Asp81 and Ser139). 35 Isolation from Taxillus sutchuenensis herba identified isosakuranetin (23), homoeriodictyol-7-O-β-D-glucopyranoside (24) and viscumneoside I (25). These compounds inhibit NS3 protease with IC50 values of 234.4±2.2 mM, 68.9±0.4 mM and 62.3±2.0 mM, respectively.…”
Section: Methodsmentioning
confidence: 99%